FILM ANIMASI SISI LAIN DARI CERITA MALIN KUNDANG - BAYU SUGARA, Hendra Afriwan, S.Sn., M.Sn., San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Minangkabau known as the realm of Minangkabau, this culture is also known for its unique culture. The uniqueness of the Minangkabau culture led to the country being targeted viewfinder tourists. A of the unique culture of Minangkabau are many folklore that has grown , especially in Indonesia.Malin Kundang is interesting story , but the story malin kundang have negative side circulating in the people, that youth minang as a rebellious child, negative side can be seen from another viewpoint that Malin Kundang story can be developed to reduce the negative side of the story, and also appeal to new areas that will generate a new economy for own people . it needed a promotion in the media that attract one of which is the medium of animation . Animation is one of the powerful media in the promotion of culture , because many enthusiasts of animation fans .From the analysis of we found that one medium that is very interesting that the animation is expected to attract the interest of children and adolescents had to remain familiar with their own unique culture. a creative concept to develop our own folklore believed to be able to attract the attention of children and adolescents in order to return love and are proud of their own culture With the completion of this animated film is expected to be another emerging young animators , so enterprising culture exhibiting itself in the arena of film animation.Keywords : Promosi, Folklore, Animation